Robust estimation of (partial) autocorrelation - Dürre, Alexander; Fried, Roland; Liboschik, Tobias (Technische Universität Dortmund, 2014)
The autocorrelation function (acf) and the partial autocorrelation function (pacf) are elementary tools of linear time series analysis. The sensitivity of the conventional sample acf and pacf to outliers is well known. We review robust estimators and evaluate their performances in different data situations considering Gaussian scenarios with and without outliers in a simulation study.
Discussion Paper / SFB 823;12/2014
Keywords: autocovariance; correlogram; time series; outliers; 310; 330; 620